Point-of-care ultrasound in the evaluation of STEMI patients - Wainstein, Marco Vugman; Machado, Guilherme Pinheiro; Telo, Guilherme Heiden; Silveira, Anderson Donelli da; Nasi, Luiz Antônio; Araujo, Gustavo Neves de (Frontiers in Cardiovascular Medicine, 2025)
BackgroundST-elevation myocardial infarction (STEMI) remains a leading cause of morbidity and mortality globally. Early risk stratification and detection of complications are critical for optimizing patient outcomes. Point-of-care ultrasound (POCUS) has emerged as a valuable bedside tool in the acute evaluation of STEMI patients.ObjectivesTo explore the role of POCUS in the early assessment of STEMI patients, focusing on its diagnostic and prognostic utility.MethodsA comprehensive review of current literature was conducted, examining the application of POCUS in STEMI.ResultsLung ultrasound (LUS) enables rapid detection of pulmonary congestion through the identification of B-lines, offering superior sensitivity compared to traditional methods. Left ventricular outflow tract velocity-time integral (LVOT-VTI) provides a quantitative assessment of stroke volume and cardiac output, aiding in the identification of low-flow states. Integrating these modalities enhances hemodynamic evaluation. Moreover, a systematic POCUS assessment may facilitate early detection of high-risk patients with acute heart failure or cardiogenic shock, as well as the identification of mechanical complications.ConclusionsThe incorporation of POCUS, specifically LUS and LVOT-VTI, into the early evaluation of STEMI patients enhances diagnostic accuracy and prognostic assessment. Future research should focus on standardizing protocols and evaluating the impact of POCUS-guided management on patient outcomes.